Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine by heptavalent manganese at environmentally relevant pH - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The rapid increase in the population across the world has increased the consumption of pharmaceutical substances. These pharmaceutical substances have penetrated into the water through various ways. Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine (AZT) by heptavalent manganese was studied for the first time. The values of pH-dependent apparent second-order rate constant show that Ru3+ accelerates the rate of the oxidative degradation of AZT by heptavalent manganese eight times faster than uncatalyzed reaction. Ru3+ catalytic oxidative degradation of AZT by heptavalent manganese was greatly depending on the pH. The removal of the AZT by heptavalent manganese in the presence of Ru3+ shows unit order with respect to heptavalent manganese, Ru3+, and AZT. The influences of dielectric constant, ionic strength, pH, addition of monomer, variation in catalyst concentration, etc. on the rate of the reaction were studied thoroughly and discussed in detail. The eight different products produced during the reaction were analyzed using the high-resolution mass spectrometry. Activation parameters were determined from variation in temperature during the reaction. The catalytic plausible mechanism was projected in which Ru3+ is oxidized to higher oxidation states of ruthenium by heptavalent manganese at environmentally relevant pH.
Keywords: Azidothymidine; catalysis; Degradation; Heptavalent manganese; kinetics; Mechanism

Morphological and molecular characterization of Penicillium rubens sp.nov isolated from poultry feed - Sawant, Amol M.; Vankudoth, Ramu; Navale, Vishwambar; Kumavat, Rajkamal; Kumari, Prabla; Santhakumari, B.; Vamkudoth, Koteswara Rao (Indian Phytopathology, 2019)
Fungi are the second largest group of eukaryotic organisms, estimates ranging from 2.2 to 3.8 million and 120,000 currently accepted species. Unfortunately, identification of Penicillium species is an overwhelming task even for taxonomic experts. In the current study, we isolated identified and morphologically characterized Penicillium rubens strain NCIM-1397. Molecular characterization of P. rubens by multilocus sequence analysis (MLSA) of internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), NL (D1/D2 region) and LR (large subunit region) gene. Conversely, BenA gene differentiated P. rubens from P. chrysogenum. Moreover, Vitek MS, Matrix-assisted laser desorption ionization–time of flight mass spectrometer (MALDI-TOF–MS) failed to discriminate to strain level. Metabolic profiling of P. rubens enable to produce roquefortine C, chrysogine, meleagrine, sorbicillin and non-producers for industrially important metabolite, penicillin determined by LC–MS. Even, In addition, even molecular detection of penicillin biosynthetic pathway genes, PcbC, PenDE and Phl were negative by PCR. Nevertheless, P. rubens showed 90–100% toxicity/pathogenicity on seed germination of sorghum (Sorghum bicolor) and no further development of coleoptiles, radicle and leaf length observed. Also, it showed non-toxic to animal cell determined on Human foreskin fibroblast (HFF) cell line by In-Vitro.

Multiple-parallel-protease digestion coupled with high-resolution mass spectrometry: an approach towards comprehensive peptide mapping of therapeutic mAbs - Pradhan, Gauri; Sneha, J. M.; Sonwane, Babasaheb P.; Santhakumari, B.; Rao, Alka; Kulkarni, Mahesh J. (Journal of Proteomics, 2021)
Therapeutic monoclonal antibodies (mAbs) are structurally large and complex molecules. To be safe and efficacious, a biosimilar mAb must show high similarity to its reference product in Critical Quality Attributes (CQA). mAbs are highly sensitive to protein expression, production, manufacturing, supply chain, and storage conditions. All these factors make biosimilar mAbs intrinsically susceptible for variability during production. Accordingly, several lots of references and tests are required to establish the biosimilarity of a test mAb. The primary structure is a CQA of a mAb affecting its safety and efficacy. Here, we apply peptide mapping as an analytical method to decipher the primary structure and associated modifications for a quick quality assessment of TrastuzumAb and RituximAb innovator and biosimilar. A multiple-parallel-protease digestion strategy followed by high-resolution mass spectrometric analysis consistently achieved 100% sequence coverage along with reliable detection of post-translational modifications. Additionally, the use of supporting methods such as intact mass analysis and circular dichroism helped us to decipher the primary and higher order structures of these mAbs. We identify discernible variations in the profile of the innovator and biosimilar mAbs and validate the method for quick yet deep comparability analysis of the primary structure of biosimilar mAbs sold in the market. Significance: Peptide mapping using bottom-up approach is one of the most common methods for the characterization of therapeutic monoclonal antibodies. Herein, we describe a multi-parallel-protease digestion strategy using a combination of five different proteases followed by high-resolution mass spectrometric analysis with TrastuzumAb and RituximAb as an example. This resulted in a comprehensive identification of peptides with increased reliability and identification of different PTMs. Additional supporting orthogonal methods like intact mass and higher-order structure analysis helped evaluate broader conformational properties.
Keywords: LC-MS/MS; PTM; RituximAb; Therapeutic monoclonal antibodies; TrastuzumAb